Evaluation of a PCR/ESI‐MS platform to identify respiratory viruses from nasopharyngeal aspirates. Issue 11 (20th May 2015) - Lin, Yong; Fu, Yongfeng; Xu, Menghua; Su, Liyun; Cao, Lingfeng; Xu, Jin; Cheng, Xunjia
<x xml:space="preserve">Abstract</x> Acute respiratory tract infection is a major cause of morbidity and mortality worldwide, particularly in infants and young children. High‐throughput, accurate, broad‐range tools for etiologic diagnosis are critical for effective epidemic control. In this study, the diagnostic capacities of an Ibis platform based on the PCR/ESI‐MS assay were evaluated using clinical samples. Nasopharyngeal aspirates (NPAs) were collected from 120 children (<5 years old) who were hospitalized with lower respiratory tract infections between November 2010 and October 2011. The respiratory virus detection assay was performed using the PCR/ESI‐MS assay and the DFA. The discordant PCR/ESI‐MS and DFA results were resolved with RT‐PCR plus sequencing. The overall agreement for PCR/ESI‐MS and DFA was 98.3% (118/120). Compared with the results from DFA, the sensitivity and specificity of the PCR/ESI‐MS assay were 100% and 97.5%, respectively. The PCR/ESI‐MS assay also detected more multiple virus infections and revealed more detailed subtype information than DFA. Among the 12 original specimens with discordant results between PCR/ESI‐MS and DFA, 11 had confirmed PCR/ESI‐MS results. Thus, the PCR/ESI‐MS assay is a high‐throughput, sensitive, specific and promising method to detect and subtype conventional viruses in respiratory tract infections and allows rapid identification of mixed pathogens. J. Med. Virol. 87:1867–1871, 2015. © 2015 Wiley Periodicals, Inc.